(untitled) - Zemach, Dorothy E (Oxford, 2011)
Writing Research Papers is a new title in the successful Macmillan Writing Series. It introduces students to academic writing and shows them how to research an academic essay, cite references and put a paper together.
Keywords: Tiếng Anh,English language,English language,Tiếng Anh; Tu từ học,Câu hỏi, bài tập, vv,Rhetoric,Problems, exercises, etc.,Writing.,Viết